Noncovalent SUMO-interaction motifs in HIV integrase play important roles in SUMOylation, cofactor binding, and virus replication - Zheng, Yingfeng (Virol J, 2019)
BACKGROUND: HIV integrase (IN) and its cellular cofactors, including lens-epithelium-derived growth factor (LEDGF/p75), Ku70, p300, and Rad52, are subject to small ubiquitin-like modifier (SUMO) modification. In addition to covalent SUMOylation, SUMO paralogs can also noncovalently bind proteins through SUMO-interacting motifs (SIMs). However, little is known about whether HIV IN contains SIMs and the roles of these motifs. RESULTS: We searched for the amino acid sequence of HIV IN and investigated three putative SIMs of IN: SIM1 72VILV75, SIM2 200IVDI203 and SIM3 257IKVV260. Our mutational analysis showed that 200IVDI203 and 257IKVV260 are two bona fide SIMs that mediate IN-SUMO noncovalent interactions. Additionally, a cell-based SUMOylation assay revealed that IN SIMs negatively regulate the SUMOylation of IN, as well as the interaction between IN and SUMO E2 conjugation enzyme Ubc9. Conversely, IN SIMs are required for its interactions with LEDGF/p75 but not with Ku70. Furthermore, our study reveals that SIM2 and SIM3 are required for the nuclear localization of IN. Finally, we investigated the impact of IN SIM2 and SIM3 on HIV single cycle replication in CD4(+) C8166 T cells, and the results showed that viruses carrying IN SIM mutants are replication defective at the steps of the early viral life cycle, including reverse transcription, nuclear import and integration. CONCLUSION: Our data suggested that the IN(SIM)-SUMO interaction constitutes a new regulatory mechanism of IN functions and might be important for HIV-1 replication.